If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 55) = (3x + -5) Reorder the terms: (55 + x) = (3x + -5) Remove parenthesis around (55 + x) 55 + x = (3x + -5) Reorder the terms: 55 + x = (-5 + 3x) Remove parenthesis around (-5 + 3x) 55 + x = -5 + 3x Solving 55 + x = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 55 + x + -3x = -5 + 3x + -3x Combine like terms: x + -3x = -2x 55 + -2x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 55 + -2x = -5 + 0 55 + -2x = -5 Add '-55' to each side of the equation. 55 + -55 + -2x = -5 + -55 Combine like terms: 55 + -55 = 0 0 + -2x = -5 + -55 -2x = -5 + -55 Combine like terms: -5 + -55 = -60 -2x = -60 Divide each side by '-2'. x = 30 Simplifying x = 30
| 4(7)-12=-5(7)+51 | | x^6-47x^3-8= | | 0.60x+.05(12-x)=.10(-49) | | 2(12)+2x=2(x-2)+2(16) | | 4n+2+4=-6 | | 2(3x-3)+2(x-3)=(2x-1)+(2x-1)+2x | | x^6-47x^3-8=0 | | 3c-4c+1=5+2+3 | | 4y+3y=63 | | 3c+4c+1=5+2+3 | | (x+55)+(3x-5)=180 | | 0.5d=3 | | 2(3x-3)+2(x-3)=(2x-1)+(2x+1)+2x | | 7=-v-3+6 | | 4(b-2)=(5-b) | | (x+55)+(3x-5)=90 | | 4r^2-r=0 | | 6,5x-9=10,5 | | 2.5d=3 | | 2=5r-3r | | 4q+8=5y | | 6x-2(x+3)=5x-1(+2) | | -6x+5(5x+12)=-168 | | 5y+12x+6=0 | | p-4=-9+9 | | 26-(3x+2)= | | 5x-17=2x+10 | | 22=11k | | 14-x=48 | | 2c-3+9d+7-6d= | | x+(x-26)=180 | | 1h+1+2h+1=6h+6-1h+2 |